From repetition to diagnosis: art, performance, and the medicalization of academic failure (Urdimento: Revista de Estudos em Artes Cênicas, 2026)
This article analyzes the video performance Dance or Exercise on the Perimeter of a Square (1968) by Bruce Nauman, shifting repetition from a reading centered on exhaustion toward the life drive, in light of Freud. In dialogue with Jack Halberstam’s queer art of failure, unproductive repetition is interpreted as a refusal of the imperatives of progress and performance. The text articulates this perspective with the educational field, questioning assessment, psychological distress, and medicalization. Drawing on Han, Foucault, and Preciado, it defends failure as an emancipatory pedagogical category.
Keywords: failure; performance; school assessment; medicalization; art education